Pengaruh Pemberian Aromaterapi Lavender Terhadap Tingkat Kecemasan pada Akseptor KB Implan di Puskesmas Haurpanggung Kabupaten Malang Tahun 2024 - Nisa, Vera; Hidayani (Lembaga Publikasi Ilmiah Nusantara, 2024)
Introduction; In 2022, the Haurpanggung Community Health Center had a coverage of 405 people (6.61%) using MKJP for implant contraception. Fear of pain during Implant insertion is a major source of anxiety for many clients and is the reason for low implant coverage. One non-pharmacological way to reduce a person's anxiety level when an implant is being installed is with lavender aromatherapy. Objective; The aim of this research was to determine the effect of giving lavender aromatherapy on anxiety levels in birth control implant acceptors. Methodology: This research uses a quasi-experiment with a pretest posttest one group design. The population in the study included 30 implant acceptors. The sample in the research used total sampling. The instruments used were HRS-A observation sheets and technical instructions for administering lavender aromatherapy. Data analysis uses paired sample test. Research Results: The anxiety of prospective contraceptive implant acceptors before being given lavender aromatherapy was 14.40 and after the intervention was 9.57. Bivariate results show a p-value of 0.000. Conclusion: There is an effect of giving lavender aromatherapy on anxiety levels in contraceptive implant acceptors. Suggestion: It is hoped that this will provide information and increase knowledge for prospective contraceptive implant recipients to use non-pharmacological management to reduce anxiety using lavender aromatherapy.